PENINGKATAN KETERAMPILAN SOSIAL ANAK USIA 5-6 TAHUN MELALUI METODE PROYEK - Evi Puji Astuti (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2016)
This study aims to (1) understand the process of implementing the project method to improve the social skills of children aged 5-6 years in TK Islam Citra Mandiri Serang Banten 2015-2016 school year, (2) and can determine the increase of social skills of children aged 5-6 years in tk islam attack offerings self image through project methods. This type of research is a classroom action research that uses models Kemmis research and Mc Taggart. Subjects were 10 children aged 5-6 years in TK Islam Citra Mandiri Serang Banten. The object of research is social skills. Methods of data collection is done through observation, interviews and documentation. Data analysis technique conducted qualitatively and quantitatively. Indicators of success in this study was 75%. The results showed that the social skills of children increased to 86.87% from the pre-study by 32% rise in the first cycle of 50.59% of these results it can be concluded that the project method can improve the social ketrampilan children aged 5-6 years in TK Islam Citra Mandiri Serang Banten.